Systemic treatment for metastatic prostate cancer - Gwenaelle Gravis (Asian Journal of Urology)
The management of metastatic prostate cancer (mPCa) has changed over the past ten years. Several new drugs have been approved with significant overall survival benefits in metastatic castration resistant prostate cancer (PCa) including chemotherapy (docetaxel, cabazitaxel), new hormonal therapies (abiraterone, enzalutamide), Radium-223 and immunotherapy. The addition of docetaxel to androgen deprivation therapy (ADT) versus ADT alone in the castration sensitive metastatic setting has gained significant overall survival benefit particularly for high volume disease. More recently two phase III trials have assessed the efficacy of abiraterone plus prednisone plus ADT over ADT alone in newly high risk castrate sensitive mPCa. Determination of the appropriate treatment sequence using these therapies is important for maximizing the clinical benefit in castration sensitive and castration resistant PCa patients. Emerging fields are the identification of new subtypes with molecular characterization and new therapeutic targets. Keywords: Prostate cancer, Metastatic prostate cancer, Castrate sensitive metastatic prostate cancer, Abiraterone, Docetaxel